2009
DOI: 10.1371/journal.pone.0008312
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae Act as Membrane Reserves Which Limit Mechanosensitive ICl,swell Channel Activation during Swelling in the Rat Ventricular Myocyte

Abstract: BackgroundMany ion channels are preferentially located in caveolae where compartmentalisation/scaffolding with signal transduction components regulates their activity. Channels that are mechanosensitive may be additionally dependent on caveolar control of the mechanical state of the membrane. Here we test which mechanism underlies caveolar-regulation of the mechanosensitive I Cl,swell channel in the adult cardiac myocyte.Methodology/Principal FindingsRat ventricular myocytes were exposed to solution of 0.02 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 41 publications
(65 reference statements)
7
93
1
Order By: Relevance
“…This could be explained by a mechanism in which rosettecaveolae are pinched off from rosettes, or by a flattening of rosette-caveolae as rosettes traffic to the perinuclear area, preventing their identification by morphological criteria; the latter possibility is also consistent with a pinch-off of the whole rosette structure. Caveolar domains respond to tension (Kozera et al, 2009;Sinha et al, 2011), and the increase in caveolar domain complexity observed in suspended cells might therefore reflect an adaptation to sudden loss of membrane tension, reportedly occurring in such conditions (Colbert et al, 2009). In contrast, these increments in caveolar complexity parameters (number of rosettes, rosette-caveolae and rosette size) observed in dRecAA cells upon loss of cell adhesion were not observed in dKOAA cells (Fig.…”
Section: Abl Tyrosine Kinases Regulate Cav1 Inward Traffickingmentioning
confidence: 88%
“…This could be explained by a mechanism in which rosettecaveolae are pinched off from rosettes, or by a flattening of rosette-caveolae as rosettes traffic to the perinuclear area, preventing their identification by morphological criteria; the latter possibility is also consistent with a pinch-off of the whole rosette structure. Caveolar domains respond to tension (Kozera et al, 2009;Sinha et al, 2011), and the increase in caveolar domain complexity observed in suspended cells might therefore reflect an adaptation to sudden loss of membrane tension, reportedly occurring in such conditions (Colbert et al, 2009). In contrast, these increments in caveolar complexity parameters (number of rosettes, rosette-caveolae and rosette size) observed in dRecAA cells upon loss of cell adhesion were not observed in dKOAA cells (Fig.…”
Section: Abl Tyrosine Kinases Regulate Cav1 Inward Traffickingmentioning
confidence: 88%
“…However, the number of caveolae does not change as a function of sarcomere length in rabbit myocardial cells (Levin and Page, 1980), raising the possibility that caveolae flattening might occur only in vivo in certain tissues. More recent studies have shown that mechanical stretching of cells or their osmotic swelling result in the flattening of about half of the caveolae (Kozera et al, 2009;Gervasio et al, 2011;Sinha et al, 2011). Caveolae flattening is also generated by an excess of stress fibers (Echarri et al, 2012), which results in an increase in membrane tension (Tamura et al, 2010;Echarri et al, 2012).…”
Section: The Actin Cytoskeleton Regulates the Organization Of Caveolamentioning
confidence: 99%
“…5) (Balijepalli and Kamp, 2008;Kozera et al, 2009;Huang et al, 2013). Furthermore, Cav3 deficiency can lead to long QT syndrome, a frequent consequence of defective ion channel functioning (Moss and Kass, 2005).…”
Section: Caveolae Regulate Other Mechanotransduction Pathwaysmentioning
confidence: 99%
“…Moreover, Cav1 has been shown to be essential for mechanoactivation of protein kinase B (Akt) and for cell cycle progression under cyclic stretch in vitro and in vivo (Sedding et al, 2005). Recently, Kozera and colleagues demonstrated a direct role for caveolae in mechanosensing and showed that caveolae can act as a membrane reserve and attenuate volume-regulated channels activation by limiting the increase in membrane tension during cellular swelling (Kozera et al, 2009). These reports endorse the hypothesis that caveolae can sense and respond to changes in membrane tension.…”
Section: Mechanosensingmentioning
confidence: 99%